Peran Program Makan Bergizi Gratis dalam Membentuk Karakter dan Semangat Belajar Siswa Sekolah Dasar - Indra Kurniawan Siregar; Riska Melinda; Nur Mawaddah; Khalimatus Sakdiah; Siti Khodijah Rangkuti; Khoirunnisa Lubis; Nabila Az-zahra; Anggun Paraditha; Nuraini Nuraini (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
The free nutritious meal program is one of the efforts to improve students' health and educational quality at the elementary school level. This study aims to determine the role of the free nutritious meal program in shaping students’ character and enhancing their learning motivation. The research employs a descriptive qualitative approach, with research subjects consisting of students, teachers, and school staff. Data collection techniques include observation, interviews, and documentation. The results show that the implementation of the free nutritious meal program has a positive impact on students’ character development, such as improving discipline, responsibility, and a sense of togetherness. In addition, the program also enhances students’ learning motivation, which is indicated by increased concentration, active participation in learning, and improved attendance. Adequate nutritional intake helps students stay focused and energized during the learning process. Therefore, the free nutritious meal program plays a significant role in supporting character building and improving students’ learning motivation, and it should be continuously developed and supported by various stakeholders to achieve optimal benefits.